Community Participation in Environmental Conservation for Sustainable Development - Fitri Rayani Siregar; Zhaoyu Chen (Journal of Community Action, 2026)
Community participation plays a decisive role in environmental conservation and sustainable development. Many conservation programs fail due to weak local engagement and limited community ownership. This study examines how community participation contributes to environmental conservation outcomes and supports sustainable development across diverse socio ecological contexts. The research adopts a qualitative systematic literature review using peer reviewed journal articles, book chapters, and international conference papers published between 2008 and 2025. Data were analyzed using thematic content analysis to identify participation models, enabling factors, and conservation impacts. The findings show that active community participation improves environmental awareness, strengthens local stewardship, enhances policy effectiveness, and increases the sustainability of conservation initiatives. Participation is most effective when supported by institutional collaboration, legal frameworks, and local knowledge integration. The study confirms that community based approaches reduce environmental degradation and support long term development goals. This research contributes to the literature by synthesizing empirical evidence across regions and proposing a structured participation framework for conservation planning. The results provide practical guidance for policymakers, practitioners, and researchers seeking to strengthen sustainable environmental governance through inclusive participation.